Between a Rock and a Hard Place: Considering “Freebirth” During Covid-19 - Greenfield, Mari; Payne-Gifford, Sophie; McKenzie, Gemma (Frontiers in Global Women's Health, 2021)
Background The global coronavirus (COVID-19) pandemic concerns all people, but has a specific effect on those who are expecting a baby during this time. The advice in the UK changed rapidly, with 14 different sets of national guidance issued within one month. Individual NHS Trusts released various guidance relating to the withdrawal of homebirth services, the closure of birth centers, restrictions on the number of birth partners (if any) allowed during labor, and whether any visitors were allowed to attend after birth. With the landscape of maternity care changing so rapidly, research was carried out to provide real time data to capture the lived experiences of expectant families. Methods A mixed methods online survey was carried out over two weeks between 10th and 24th April 2020. The survey was open to those in the third trimester of pregnancy, those who had given birth since the beginning of the ‘lockdown’ period in the UK, and the partners of pregnant women and people who were in these circumstances. The survey asked questions about how respondents’ holistic antenatal experiences had been affected, whether their plans for birth had changed, and the effect of these changes on respondents’ emotional wellbeing. Of the 1,700 responses received, 72 mentioned that they had seriously considered ‘freebirthing’ (giving birth without a healthcare professional present). Findings An analysis of the respondents’ reasons for considering freebirth was conducted, finding that reasons for considering freebirth were complex and multifaceted. Lesbian, bisexual, pansexual and queer women were more likely to have considered freebirth than heterosexual people (p<0.001). Conclusions Considering giving birth without a healthcare professional present is unusual in the Global North and represents an emerging field of study. The literature examining the reasons that people consider freebirth shows a variety of underlying motivations. A global pandemic represents a new factor in such considerations. The findings from this research can help inform maternity service planning in future crises.